Kualitas Laporan Keuangan, Asimetri Informasi dan Efisiensi Investasi Pada Perusahaan Pertambangan - Purba, Ida Ayu Candrasatyani; Suaryana, I Gusti Ngurah Agung (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 1 (2018), 2018)
Presentation of qualified financial statements can lead to optimal investment activity, especially supported by the low information asymmetry between manager and shareholders. The research purpos es to prove empirically and explain the impact of financial statements quality on information asymmetry and its impact on investment efficiency. Object of the research is mining companies listed on the Indonesia Stock Exchange year 2013-2015.Determination of the sample is purposive sampling, so that there are 69 companies sampled.Path analysis is a data analysis technique to obtain the results. The analysis result found that the quality of financial statement has a negative effect on information asymmetry and has a positive effect on investment efficiency, information asymmetry has a negative effect on investment efficiency, and only some of the information asymmetry contributes to the quality of the financial statements on investment efficiency. Keywords : quality of financial reports, information asymmetry, investment efficiency